Balanga City Clay Heritage and Research Institute helping Balanga City form a solid identity in the future - Bonites, Ronn Dayniel Matthew C. (College of Architecture, University of the Philippines Diliman, 2020)
Balanga City was named after its high-quality earthenware that was well-sought in the past. Nowadays, it is barely even known for its pots nor is it even associated with them anymore asides from the name. Decades of declining interest and profitability in the craft has left it neglected until there were no successors left who knew how to make them, putting their heritage at risk. With Balanga's rise as one of the top emerging cities in the Philippines, the risk of losing Balanga's namesake and identity is only made greater by the rapid development across the city. This study aims to help Balanga City reconnect with and develop a new identity for themselves rooted in their pottery heritage through architecture. The project will be a mixed-use Clay Workshop-cum-Research Institute located in the birthplace of Balanga's clay pots. The project envisions that through exposure and involvement with the craft, the people of Balanga, especially the younger generations, will reconnect with their heritage and develop it into something new that is entirely their own, reviving what was once lost.